Mineral nutrition evolution in the formation of fruit tree rootstocks and seedlings - Natale, William; de Lima Neto, Antonio João; Rozane, Danilo Eduardo [UNESP]; Parent, Léon Etienne; de Medeiros Corrêa, Márcio Cleber (FapUNIFESP (SciELO), 2018)
The importance of mineral nutrition to the various plant species has been recognized for many years. Since nutrients are directly linked to physiological and metabolic processes, they promote the growth of rootstocks and seedlings, contributing to the formation of more productive orchards. As a consequence of the lack of technical information for most fruit trees, fertilization in nurseries has still been carried out empirically, sometimes underestimating or overestimating nutritional requirements and compromising the quality of plants produced. Given the importance of mineral nutrition in the formation of high-quality seedlings and the lack of scientific information on the topic, the aim of the present review was to raise interest in further research, and contribute to produce nutritionally balanced fruit seedlings.
Evolução da nutrição mineral na formação de porta-enxertos e mudas de frutíferas
Keywords: Fertilization; Nurseries; Nutritional diagnosis